Rare Case of Gut-associated Lymphoid Tissue Carcinoma in the Sigmoid Colon of a Very Elderly Patient: A Case Report - Kou Kanesada; Kazuhiko Yoshimatsu; Yoshitomo Ito; Shuya Yano; Masaaki Hori; Masaharu Higashida; Toshimasa Okada; Shunji Endo; Yoshinori Fujiwara; Yasuto Fujimoto; Tatsushi Shiomi; Tomio Ueno (Journal of the Anus, Rectum and Colon)
Colorectal cancer with gut-associated lymphoid tissue (GALT) carcinoma histopathology is particularly rare in very elderly patients. GALT is characterized by submucosal localization and prominent lymphoid infiltration with germinal center formation within tumor-infiltrating lymphocytes. This study aims to report a case of colorectal cancer with GALT carcinoma histopathology in a very elderly patient and to provide a comprehensive literature review. In this case, a 90-year-old female presented with an irregularly elevated tumor in the sigmoid colon, diagnosed via colonoscopy. Computed tomography revealed no lymph node or distant metastases. The patient underwent laparoscopy-assisted sigmoid colon resection with D3 dissection. Histopathological examination revealed well-differentiated adenocarcinoma in the submucosal layer with partial invasion into the muscle layer. Lymphocytes, along with lymph follicles, proliferated compressively in the stroma surrounding the tumor glands. Immunohistochemical analysis showed lost expression of mismatch repair proteins, MLH1 and PMS2, consistent with the tumor immunohistochemistry profile. B cells (CD20- and CD79a-positive) were generally distributed in and around the lymph follicles, while T cells (CD3-positive) were primarily located between the lymph follicles. This case highlights the rare histopathology of GALT carcinoma in colorectal cancer and underscores the importance of considering such diagnoses in elderly patients with colorectal tumors.